A bimetallic supported Ti-SBA-15 catalyst, a preparation method and application thereof
By preparing a CoCu bimetallic supported Ti-SBA-15 catalyst, the problem of poisoning of noble metal catalysts was solved, and the efficient conversion and high selectivity of glycerol selective oxidation to tartaric acid were achieved, reducing production costs.
Patent Information
- Application Number
- CN202410253835.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2026-07-10
- Estimated Expiration
- 2044-03-06
AI Technical Summary
Existing noble metal catalysts are prone to catalytic poisoning by reaction intermediates in the selective oxidation of glycerol to tartaric acid, resulting in high costs and difficulty in industrialization.
The Ti-SBA-15 catalyst supported by CoCu bimetallic materials was prepared by loading cobalt and copper precursors onto a Ti-SBA-15 support via room temperature impregnation and calcining at 500–550 °C.
It achieves high efficiency conversion of glycerol (>60%) and high selectivity of tartaric acid (>50%), reduces production costs, and has a simple preparation process with mild conditions.
Smart Images

Figure CN117899926B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a catalyst and its application, specifically to a bimetallic supported Ti-SBA-15 catalyst, its preparation method, and its application. Background Technology
[0002] With the depletion of fossil fuels such as coal, oil, and natural gas, and the deterioration of the ecological environment, modern society urgently needs to develop renewable resources and energy, and on this basis, develop economical, energy-saving, and environmentally friendly processes to achieve the sustainable production of fuels and fine chemicals. Compared to fossil fuels, biodiesel, as a renewable liquid fuel, has advantages such as high cetane number, low pollution, easy degradation, and good combustion performance, and is considered a promising alternative to traditional fossil fuels, leading to its widespread development and utilization. However, large-scale production of biodiesel through transesterification results in an oversupply of crude glycerol, a byproduct, causing a sharp drop in price and hindering further promotion of biodiesel. Therefore, converting glycerol into high-value-added chemicals is one of the keys to promoting biodiesel.
[0003] Glycerol is a highly functionalized molecule with three hydroxyl groups. It can be used to derive numerous high-value chemical intermediates through reactions such as oxidation, hydrogenolysis, dehydration, esterification, oxidative carbonylation, transesterification, and polymerization. Selective oxidation of glycerol can yield expensive chemicals such as tartaric acid, dihydroxyacetone, glyceric acid, and glyceraldehyde. Tartaric acid has wide applications in the pharmaceutical field; it can inhibit the conversion of carbohydrates into fat in the body, preventing fat accumulation and thus having effects on weight loss and prevention of coronary heart disease, making it suitable as a drug for treating obesity. It can also be used in the synthesis of detergents and chelating agents.
[0004] Currently, most catalysts used for the selective oxidation of glycerol employ noble metals as the active component. Pt, Au, and Ag are widely used noble metal catalysts; however, these catalysts suffer from several drawbacks: their active sites are easily poisoned by reaction intermediates, their catalytic activity is highly dependent on size, they are scarce and costly, and they are difficult to industrialize. Therefore, developing low-cost, highly efficient, and stable catalysts is a pressing issue. Summary of the Invention
[0005] Objective of the Invention: The key objective of this invention is to provide a method for preparing a non-precious metal CoCu supported Ti-SBA-15 catalyst and its application. This method is simple to operate, operates under mild conditions, and has low production costs, making it promising for industrial production. This invention aims to provide a low-cost, highly efficient, and stable bimetallic supported Ti-SBA-15 catalyst; it also aims to provide a method for preparing the bimetallic supported Ti-SBA-15 catalyst; and it further aims to provide an application of the bimetallic supported Ti-SBA-15 catalyst in the selective oxidation of glycerol to tartaric acid.
[0006] Technical solution: The bimetallic supported Ti-SBA-15 catalyst of the present invention, wherein the bimetal is CoCu, the loading of CoCu accounts for 5 to 25 wt% of the catalyst, and the mass ratio of Co to Cu is 0.25 to 4:1.
[0007] The preparation method of the bimetallic supported Ti-SBA-15 catalyst includes the following steps: impregnating cobalt and copper precursors with Ti-SBA-15 support at room temperature (equal volume impregnation composite method) to obtain a mixed solution, drying and then calcining to obtain the bimetallic supported Ti-SBA-15 catalyst.
[0008] Preferably, the cobalt precursor is cobalt nitrate or cobalt chloride; the copper precursor is copper nitrate, copper sulfate or copper chloride.
[0009] Preferably, the calcination temperature is 500–550°C, the calcination time is 2–4 h, the heating rate is 1–5°C / min, and the impregnation time is 12–48 h.
[0010] Preferably, the preparation method of the Ti-SBA-15 support includes the following steps: (1) dissolving the surfactant poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer in hydrochloric acid solution and stirring to form solution A; (2) adding silicon source, titanium source and acetylacetone dropwise to solution A and stirring to form solution B. Then, transferring solution B into a reaction vessel and aging it at 80-150°C to obtain a white solid. After filtration, washing and drying, it is calcined at 500-550°C to obtain the Ti-SBA-15 support.
[0011] Preferably, the concentration of the hydrochloric acid solution in step (1) is 1-2 mol / L; the mass-to-volume ratio of the surfactant to the hydrochloric acid is 3-6 g / 100-250 mL.
[0012] Preferably, in step (2), the silicon source is tetraethyl orthosilicate and the titanium source is tetrabutyl titanate. The silicon-titanium molar ratio in the silicon source tetraethyl orthosilicate and the titanium source tetrabutyl titanate is 10-100:1, and the molar ratio in the tetrabutyl titanate and acetylacetone is 1:0.4-1.2.
[0013] Preferably, the stirring time for solution A is 2–12 h, and the stirring temperature is 30–50 °C; the stirring time for solution B is 24–72 h, and the stirring temperature is 30–50 °C; the aging time is 12–48 h, and the calcination time is 6–8 h.
[0014] The bimetallic supported Ti-SBA-15 catalyst can be used in the selective oxidation of glycerol to prepare tartaric acid.
[0015] The specific steps of the selective oxidation of glycerol to prepare tartaric acid include: dissolving 0.5–0.6 g of glycerol in 20–30 mL of deionized water, dissolving 0.8–0.9 g of sodium hydroxide in 10–20 mL of deionized water, transferring the above solution and 0.1–0.5 g of catalyst to a three-necked flask, adding 0.6–3 mL of 30% hydrogen peroxide dropwise, stirring the reaction at 40–100 °C for 2–12 h, and filtering to separate the catalyst.
[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The CoCu supported Ti-SBA-15 catalyst is a Ti-modified SBA-15 molecular sieve with ordered mesoporous channels as a support. The pore restriction effect of SBA-15 molecular sieve is used to regulate the adsorption and diffusion of reactants and products, thereby improving the high efficiency and selectivity of the target product. On the basis of the pore restriction characteristics of molecular sieve SBA-15, Ti is introduced to modify the molecular sieve. The introduction of Ti improves the anchoring and regulation of the metal active components, which is conducive to the conversion of glycerol to tartaric acid, and further improves the selectivity of tartaric acid. The introduction of Co and Cu bimetals not only reduces the production cost of the reaction, but also the oxides of the two metals have a synergistic effect on the catalytic oxidation reaction. Compared with the single metal, it has a higher selectivity for the target product tartaric acid, realizing the high efficiency conversion of glycerol (conversion rate > 60%) and the high selectivity of tartaric acid (selectivity > 50%). (2) The preparation process is simple, the cost is low, and the reaction conditions are mild. Attached Figure Description
[0017] Figure 1 The image shows the XRD pattern of CoCu / Ti-SBA-15 prepared in Example 1.
[0018] Figure 2 The image shows the FT-IR spectrum of CoCu / Ti-SBA-15 prepared in Example 1.
[0019] Figure 3 The image shows a SEM image of CoCu / Ti-SBA-15 prepared in Example 1.
[0020] Figure 4The graph shows a performance comparison between the CoCu bimetallic supported Ti-SBA-15 catalyst with the same metal loading in Application Example 1 and the Cu supported Ti-SBA-15 catalyst in Comparative Example 1 (including the conversion of glycerol and the selectivity of tartaric acid). Detailed Implementation
[0021] The technical solution of the present invention will be further described below with reference to the embodiments and accompanying drawings.
[0022] Example 1
[0023] (1) Dissolve 6.0g of surfactant poly(ethylene oxide-poly(propylene oxide-poly(ethylene oxide) triblock copolymer), abbreviated as P123, in 225mL of 2mol / L hydrochloric acid solution and stir at 40℃ for 4h until it dissolves to form solution A.
[0024] (2) Silicon-derived tetraethyl orthosilicate, titanium-derived tetrabutyl titanate (the molar ratio of Si in tetraethyl orthosilicate to Ti in tetrabutyl titanate is 20) and acetylacetone were slowly added dropwise to solution A (the molar ratio of tetrabutyl titanate to acetylacetone is 1:0.6). After stirring at 40°C for 24 h, solution B was formed. Solution B was then transferred to a hydrothermal reactor and aged at 100°C for 24 h to obtain a white solid. After filtration and washing three times, it was dried into a white powder and calcined at 550°C for 6 h (the heating rate was 5°C / min) to obtain the Ti-SBA-15 support.
[0025] (3) 0.074 g of Co(NO3)2 and 0.057 g of Cu(NO3)2 aqueous solution (total water mass is 1.8 g) were added dropwise to 0.3 g of Ti-SBA-15 support under ultrasonication. After stirring at room temperature for 24 h, C solution was obtained. C solution was dried in an oven at 100 °C and then calcined at 550 °C for 4 h in a muffle furnace (heating rate is 5 °C / min) to prepare bimetallic CoCu supported Ti-SBA-15 catalyst, in which the Co loading is 5 wt% and the Cu loading is 5 wt%, hence it is denoted as Co1Cu1 / Ti-SBA-15.
[0026] Figure 1 The image shows the XRD pattern of the Co1Cu1 / Ti-SBA-15 catalyst in this embodiment. As can be seen from the image, Co exists in the form of cobalt tetroxide and Cu exists in the form of copper oxide. Figure 2 This is the FT-IR spectrum of the Co1Cu1 / Ti-SBA-15 catalyst in this embodiment. The spectrum shows that at 960 cm⁻¹... -1 The absorption peaks that appeared were attributed to the stretching vibrations of the Ti-O-Si bond, proving the successful synthesis of Ti-SBA-15. Figure 3This is a SEM image of the Co1Cu1 / Ti-SBA-15 catalyst in this embodiment. As can be seen from the image, the catalyst has a short rod-shaped morphology, and the rods are bundled together, which is a typical SBA-15 morphology.
[0027] Comparative Example
[0028] 0.114 g of Cu(NO3)2 aqueous solution (total water mass 1.8 g) was added dropwise to 0.3 g of Ti-SBA-15 support under ultrasonication. After stirring at room temperature for 24 h, the solution was dried in an oven at 100 °C and then calcined in a muffle furnace at 550 °C for 4 h (heating rate 5 °C / min) to prepare a single-metal Cu-supported Ti-SBA-15 catalyst with a Cu loading of 10 wt%, denoted as Cu / Ti-SBA-15.
[0029] Example 2
[0030] (1) Dissolve 6.0g of surfactant P123 in 225mL of 2mol / L hydrochloric acid solution and stir at 40℃ for 4h until it dissolves to form solution A.
[0031] (2) Silicon-derived tetraethyl orthosilicate, titanium-derived tetrabutyl titanate (the molar ratio of Si in tetraethyl orthosilicate to Ti in tetrabutyl titanate is 20) and acetylacetone were slowly added dropwise to solution A (the molar ratio of tetrabutyl titanate to acetylacetone is 1:0.6). After stirring at 40°C for 24 h, solution B was formed. Solution B was then transferred to a hydrothermal reactor and aged at 100°C for 24 h to obtain a white solid. After filtration and washing three times, it was dried into a white powder and calcined at 550°C for 6 h (the heating rate was 5°C / min) to obtain the Ti-SBA-15 support.
[0032] (3) 0.074 g of Co(NO3)2 and 0.114 g of Cu(NO3)2 aqueous solution (total water mass is 1.8 g) were added dropwise to 0.3 g of Ti-SBA-15 support under ultrasonication. After stirring at room temperature for 24 h, C solution was obtained. C solution was dried in an oven at 100 °C and then calcined in a muffle furnace at 550 °C for 4 h (heating rate is 5 °C / min) to prepare bimetallic CoCu supported Ti-SBA-15 catalyst, wherein the Co loading is 5 wt% and the Cu loading is 10 wt%.
[0033] Example 3
[0034] (1) Dissolve 6.0g of surfactant P123 in 225mL of 2mol / L hydrochloric acid solution and stir at 40℃ for 4h until it dissolves to form solution A.
[0035] (2) Silicon-derived tetraethyl orthosilicate, titanium-derived tetrabutyl titanate (the molar ratio of Si in tetraethyl orthosilicate to Ti in tetrabutyl titanate is 20) and acetylacetone were slowly added dropwise to solution A (the molar ratio of tetrabutyl titanate to acetylacetone is 1:0.6). After stirring at 40°C for 24 h, solution B was formed. Solution B was then transferred to a hydrothermal reactor and aged at 100°C for 24 h to obtain a white solid. After filtration and washing three times, it was dried into a white powder and calcined at 550°C for 6 h (the heating rate was 5°C / min) to obtain the Ti-SBA-15 support.
[0036] (3) 0.074 g of Co(NO3)2 and 0.228 g of Cu(NO3)2 aqueous solution (total water mass is 1.8 g) were added dropwise to 0.3 g of Ti-SBA-15 support under ultrasonication. After stirring at room temperature for 24 h, C solution was obtained. C solution was dried in an oven at 100 °C and then calcined in a muffle furnace at 550 °C for 4 h (heating rate is 5 °C / min) to prepare bimetallic CoCu supported Ti-SBA-15 catalyst, wherein the Co loading is 5 wt% and the Cu loading is 20 wt%.
[0037] Example 4
[0038] (1) Dissolve 6.0g of surfactant P123 in 225mL of 2mol / L hydrochloric acid solution and stir at 40℃ for 4h until it dissolves to form solution A.
[0039] (2) Silicon-derived tetraethyl orthosilicate, titanium-derived tetrabutyl titanate (the molar ratio of Si in tetraethyl orthosilicate to Ti in tetrabutyl titanate is 20) and acetylacetone were slowly added dropwise to solution A (the molar ratio of tetrabutyl titanate to acetylacetone is 1:0.6). After stirring at 40°C for 24 h, solution B was formed. Solution B was then transferred to a hydrothermal reactor and aged at 100°C for 24 h to obtain a white solid. After filtration and washing three times, it was dried into a white powder and calcined at 550°C for 6 h (the heating rate was 5°C / min) to obtain the Ti-SBA-15 support.
[0040] (3) 0.148 g of Co(NO3)2 and 0.057 g of Cu(NO3)2 aqueous solution (total water mass 1.8 g) were added dropwise to 0.3 g of Ti-SBA-15 support under ultrasonic action. After stirring at room temperature for 24 h, C solution was obtained. C solution was dried in an oven at 100 °C and then calcined at 550 °C for 4 h in a muffle furnace (heating rate of 5 °C / min) to prepare bimetallic CoCu supported Ti-SBA-15 catalyst, wherein the Co loading was 10 wt% and the Cu loading was 5 wt%.
[0041] Example 5
[0042] (1) Dissolve 6.0g of surfactant P123 in 225mL of 2mol / L hydrochloric acid solution and stir at 40℃ for 4h until it dissolves to form solution A.
[0043] (2) Silicon-derived tetraethyl orthosilicate, titanium-derived tetrabutyl titanate (the molar ratio of Si in tetraethyl orthosilicate to Ti in tetrabutyl titanate is 20) and acetylacetone were slowly added dropwise to solution A (the molar ratio of tetrabutyl titanate to acetylacetone is 1:0.6). After stirring at 40°C for 24 h, solution B was formed. Solution B was then transferred to a hydrothermal reactor and aged at 100°C for 24 h to obtain a white solid. After filtration and washing three times, it was dried into a white powder and calcined at 550°C for 6 h (the heating rate was 5°C / min) to obtain the Ti-SBA-15 support.
[0044] (3) 0.296 g of Co(NO3)2 and 0.057 g of Cu(NO3)2 aqueous solution (total water mass 1.8 g) were added dropwise to 0.3 g of Ti-SBA-15 support under ultrasonication. After stirring at room temperature for 24 h, C solution was obtained. C solution was dried in an oven at 100 °C and then calcined at 550 °C for 4 h in a muffle furnace (heating rate of 5 °C / min) to prepare a bimetallic CoCu supported Ti-SBA-15 catalyst, in which the Co loading was 20 wt% and the Cu loading was 5 wt%.
[0045] Application examples
[0046] 0.553 g of glycerol was dissolved in 20 mL of deionized water, and 0.8 g of sodium hydroxide was dissolved in 10 mL of deionized water. The Co1Cu1 / Ti-SBA-15 catalyst prepared in Example 1 and the Cu / Ti-SBA-15 catalyst prepared in Comparative Example 1 were added to the above solutions respectively. 1.23 mL of 30% hydrogen peroxide was added dropwise to each. The mixture was stirred at 80 °C for 4 h, and the catalyst was separated by filtration.
[0047] Tests showed that the above-mentioned catalyst Co1Cu1 / Ti-SBA-15 achieved a glycerol conversion rate of 63.8% and a selectivity of 54.5% for the selective oxidation of glycerol to tartaric acid.
[0048] Figure 4This is a comparison of the catalytic performance of the CoCu bimetallic supported Ti-SBA-15 catalyst with the same metal loading in this application example and the Cu supported Ti-SBA-15 catalyst in the comparative example. As can be seen from the figure, the glycerol conversion and tartaric acid selectivity of the bimetallic Co1Cu1 / Ti-SBA-15 catalyst are higher than those of the single metal Cu / Ti-SBA-15 catalyst. Therefore, the bimetallic CoCu dispersed on Ti-SBA-15 can effectively improve the catalytic activity and the selectivity of the target product.
Claims
1. The application of a bimetallic supported Ti-SBA-15 catalyst in the selective oxidation of glycerol to tartaric acid, characterized in that, The bimetal is CoCu, with the CoCu loading accounting for 5-25 wt% of the catalyst, and the mass ratio of Co to Cu being 0.25-4:
1.
2. The application according to claim 1, characterized in that, The application method includes: dissolving 0.5-0.6 g of glycerol in 20-30 mL of deionized water, dissolving 0.8-0.9 g of sodium hydroxide in 10-20 mL of deionized water, mixing the above solution with 0.1-0.5 g of catalyst evenly, transferring the mixture to a three-necked flask, adding 0.6-3 mL of 30% hydrogen peroxide dropwise, stirring the mixture at 40-100 °C for 2-12 h, and filtering to separate the catalyst.
3. The application according to claim 1, characterized in that, The preparation method of the bimetallic supported Ti-SBA-15 catalyst includes the following steps: impregnating cobalt and copper precursors with Ti-SBA-15 support at room temperature to obtain a mixed solution, drying and then calcining to prepare the bimetallic supported Ti-SBA-15 catalyst.
4. The application according to claim 3, characterized in that, The cobalt precursor is cobalt nitrate or cobalt chloride; the copper precursor is copper nitrate, copper sulfate or copper chloride.
5. The application according to claim 3, characterized in that, The calcination temperature is 500~550 ℃, the calcination time is 2~4h, the heating rate is 1~5 ℃ / min, and the impregnation time is 12~48h.
6. The application according to claim 3, characterized in that, The preparation method of the Ti-SBA-15 support includes the following steps: (1) Dissolve the surfactant poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer in hydrochloric acid solution and stir to form solution A; (2) Add silicon source, titanium source and acetylacetone dropwise to solution A and stir to form solution B. Then transfer solution B into a reaction vessel and age it at 80~150 °C to obtain a white solid. After filtration, washing and drying, calcining at 500~550 °C, the Ti-SBA-15 support is obtained.
7. The application according to claim 6, characterized in that, The concentration of the hydrochloric acid solution in step (1) is 1~2 mol / L; the mass-to-volume ratio of the surfactant to hydrochloric acid is 3~6 g / 100~250 mL.
8. The application according to claim 6, characterized in that, In step (2), the silicon source is tetraethyl orthosilicate and the titanium source is tetrabutyl titanate. The silicon-titanium molar ratio in the silicon source tetraethyl orthosilicate and the titanium source tetrabutyl titanate is 10~100:1, and the molar ratio of tetrabutyl titanate to acetylacetone is 1:0.4~1.
2.
9. The application according to claim 6, characterized in that, The stirring time for solution A is 2-12 h, and the stirring temperature is 30-50 ℃; the stirring time for solution B is 24-72 h, and the stirring temperature is 30-50 ℃; the aging time is 12-48 h, and the calcination time is 6-8 h.
Citation Information
Patent Citations
Copper-based catalyst for preparing ethylene glycol and ethylene glycol monomethyl ether through hydrogenation of dimethyl oxalate and preparation method thereof
CN103566949A
Titanium modified copper-based mesoporous molecular sieve catalyst and preparation method and application thereof
CN108452823A